Ultrafine Carbon Fibers with Hollow-Porous Multilayered Structure for Supercapacitors - YILDIZ, ZEHRA (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Electrospun fibers of mixed polyacrylonitrile/polyvinyl pyrrolidine (PAN/PVP) sheath and silicone oil core were obtained by coaxial electrospinning. PVP and silicone oil were then removed from the coaxial electrospun fibers via phase separation and carbonization processes, respectively, to make the hollowporous multilayered ultrafine carbon fibers. The relationship between the morphology and electrochemical performance of ultrafine carbon fibers was investigated. Results show that the supercapacitor based on electrode of hollow-porous multilayered ultrafine carbon fibers exhibits high conductivity, fast ion diffusion, high specific capacitance (231.6 F.g(-1)), high charging/discharging efficiency (99.7%), and low internal resistance (0.2 Omega) using tetraethylammonium tetrafluoroborate in acetonitrile as electrolyte. Additionally, this work also demonstrates a great potential in the preparation of carbon nano-materials with graphene-like multilayer structure. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: hollow-porous multilayered; ultrafine carbon fiber; electrospinning; phase separation; carbonization; supercapacitor; ENERGY-STORAGE; NANOFIBERS; PERFORMANCE; ELECTRODE; BATTERY